The Effect of Problem Based Learning Model on Students’ Conceptual Understanding in Thermodynamics Assisted by PhET Simulator - Agustin, Viola Maharani; Saehana, Sahrul; Gustina, Gustina; Paramita, Ielda (UIN Alauddin Makassar, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students’ conceptual understanding of physics in topics of thermodynamics, assisted by PhE Simulator media. The study employed a quantitative approach with Quasi-Experimental design of the One Group Pretest-Posttest type. The research sample consisted of 26 students from class XI C at MAN Tolitoli, and the instrument used was a multiple-choice test comprising 20 item with five answer options. The test was based on three indicators of conceptual understanding proposed by Bloom : translation, interpretation, and extrapolation. The descriptibe analysis results showed that the students’ average conceptual understanding scores increased from 41,15 in the pretest to 81,73 in the posttest. The normality test results indicated that the data were normally distributed, and the hypothesis testing using the Paired Sampel T-Test technique showed that calculated t-valude was greater than the critical t-value (11,55 ˃ 1,71), with a significance level of α = 0,05/ these findings indicated that the implementation of the Problem Based Learning model assisted by PhET is effective in improving the quality of physics learning, espeacially for abstract topics such as thermodynamics.